Reinsurance: Substance, range and importance - Petrović-Tomić Nataša (Anali Pravnog Fakulteta u Beogradu)
Reinsurance - at least in Serbian law - represents one of the institutes of Insurance Law of whom a little is known. It should not be surprising as the contract of reinsurance traditionally is not regulated in civil codes or laws on contract of insurance. Questionable are all features of the contract of reinsurance: from the definition through the essentialia negotii to the principle of utmost good faith. That is why the paper is structured so that firstly gives definition of contract of reinsurance and explains position of reinsurance in the system of insurance. It is highlighted that the contract of reinsurance builds on the contract of insurance; which enables the further transfer of risk. It is business-to-business contract (B-2-B), concluded between insurance law experts; frequently of international character; mostly contract of adhesion, aleatory and synallagmatic contract, contract with subsequent execution, etc. The importance of reinsurance in the system of insurance is divided on three components: increase of capacity of insurance market, guarantee of acomplishment of obligations of insurer and regulatory effect on insurance. The author concludes that the contract of reinsurance is a specific business insurance contract, concluded by the insurance law experts and that represents community of interests of reinsurer and reinsured. The mentioned contract may perform its function only if the contracting parties act in a responsible manner, lege artis and respecting the principle of utmost good faith.